2014
DOI: 10.4103/0255-0857.136572
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of ventilator-associated pneumonia: Comparison between ante-mortem and post-mortem cultures in trauma patients

Abstract: Culture results of a properly collected tracheal aspirate should be taken into consideration along with Centre for Disease Control and Prevention (CDC's) diagnostic criteria to maximise the diagnosis of VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…A high prevalence of multidrug resistance is seen at our center in all genera of Gram-negative bacteria. [ 13 ] Although not reported in the present study, we have observed that not all patients suffering from VAP with the same clone of A. baumannii have a fatal outcome. [ 14 ] Thus, there must be some host immune response-driven factors which propel a patient toward a poor outcome.…”
Section: Resultscontrasting
confidence: 52%
“…A high prevalence of multidrug resistance is seen at our center in all genera of Gram-negative bacteria. [ 13 ] Although not reported in the present study, we have observed that not all patients suffering from VAP with the same clone of A. baumannii have a fatal outcome. [ 14 ] Thus, there must be some host immune response-driven factors which propel a patient toward a poor outcome.…”
Section: Resultscontrasting
confidence: 52%
“…was seen. This observation was in agreement with other researchers' like Singh et al (2010) [ 9 ] and Lalwani et al (2014) [ 28 ]. Therefore, it can be stated that VAP may be caused by a wide spectrum of bacterial pathogens but rarely due to mycotic pathogens.…”
Section: Discussionsupporting
confidence: 94%
“…VAP remains an important cause of morbidity and mortality despite advances in antimicrobial therapy, better supportive care modalities, and the use of a wide range of preventive measures [ 28 ]. It complicates the course of 8–28% of the patients on mechanical ventilation [ 28 ]. In the present study, the rate of VAP per 1000 device days was found to be 3.3, which is quite low in comparison to that reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…All the specimens were immediately processed in the Department of Microbiology. The specimens were directly inoculated onto MacConkey agar and Blood agar media by quantitative culture method [6]. The plates were kept for overnight incubation at 37 °C.…”
Section: Methodsmentioning
confidence: 99%